Preparation method of diamond / copper composite material

Through the methods of mixing ingredients and hot pressing sintering, the problems of high temperature, low thermal conductivity and uneven particle dispersion in the preparation of diamond copper composites are solved, and diamond/copper composites with high thermal conductivity, low thermal expansion coefficient and high tensile strength are achieved.

CN119506650APending Publication Date: 2025-02-25SUZHOU UNIV OF SCI & TECH +1

Patent Information

Application Number
CN202411644280.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing preparation methods of diamond copper composites have problems such as high processing temperature, direct contact between diamond particles and molten copper, resulting in a reduced thermal conductivity, and uneven dispersion of diamond particles in the composite materials.

Method used

By combining ingredients and hot press sintering, the preparation of matrix material and reinforcement filler material, including the interfacial reaction using Ti and silicon carbide powder to generate titanium silicon carbide, improve the adhesion between diamond and copper, and adjust the surface energy state of the particles through a ball milling process, and finally vacuum-heat press sintering.

Benefits of technology

The high thermal conductivity and low thermal expansion coefficient of diamond/copper composite materials are achieved, the tensile strength reaches 500MPa, the thermal conductivity reaches 715W/m·K, and the diamond particles are evenly dispersed in the composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506650A_ABST
    Figure CN119506650A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a diamond / copper composite material, which comprises the steps of ingredient mixing and hot pressed sintering: preparing copper powder, metal Ti / nonmetal carbide and Cr or Mn powder into a base material, and uniformly mixing large-particle diamond and small-particle diamond to prepare a reinforcing body filling material; then the base material and the reinforcement filling material are taken and placed in a container to be mixed, after mixing, grinding is conducted in the environment of vacuumizing and filling of high-purity argon, and mixture powder is obtained; and the mixture powder is subjected to vacuumizing hot pressing sintering, then in the vacuum state, a heating system is closed, natural cooling is conducted, high-purity nitrogen is charged into a sintering furnace cavity, the cavity is opened after the pressure inside and outside the cavity is equal, and the diamond / copper composite material is obtained. According to the method provided by the technical scheme, the problems that the cost is high, the heat conductivity is low, diamond particles are not uniformly dispersed in the composite material and the diamond particles fall off due to poor wetting when the diamond / copper composite material is prepared by a metal permeation technology can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a method for preparing a high thermal conductivity diamond / copper composite material. Background Art

[0002] With the continuous improvement of chip integration, electronic packaging is developing in the direction of miniaturization, lightness and high performance, which makes the operating temperature of the circuit continue to rise, and the heat generation rate per unit volume of the system continues to increase, resulting in unstable system operation. In order to obtain stable performance, it is necessary to improve the heat dissipation conditions. Therefore, the importance of electronic packaging in the field of microelectronics is constantly increasing, and the demand for new electronic packaging materials is also increasing. High-quality diamond is the material with the highest known thermal conductivity in the world, which can reach 1800-2000w / (m·k). It is an insulator at room temperature and has the characteristics of low dielectric constant and low thermal expansion coefficient. However, single diamond is not easy to make packaging materials, and the cost is very high. It is more ideal to make it into a metal-based composite material. Metallic copper has excellent electrical and thermal conductivity. The thermal conductivity of metallic copper is 404w / (m·k) and the thermal expansion coefficient is 16.8×10-6 / k. Diamond copper-based composite materials have the advantages of higher thermal conductivity than traditional metal alloys and aluminum nitride ceramic materials, matching thermal expansion coefficient with semiconductor materials, and corrosion resistance in seawater salt spray environment. Therefore, it is suitable for electronic packaging and thermal management materials such as phased array radar.

[0003] The difficulties in preparing diamond copper-based composite materials are: (1) The wettability of diamond and copper is poor. The wetting angle between diamond and copper is 145° at 1150°C; (2) There is no solid-phase reaction between diamond and copper at high temperature, and carbon has no solid solubility in copper, so it is difficult to sinter a dense composite material. Diamond surface modification, such as adding strong carbide-forming elements, can improve the wettability of diamond and copper to a certain extent, but the modification also brings about the new problem of increasing the interfacial thermal resistance, affecting the thermal conductivity and thermal expansion coefficient of the diamond copper-based composite material. (3) Diamond graphitization problem. In air, diamond may be completely graphitized above 773K. Under vacuum conditions, diamonds at 970K-1670K begin to partially graphitize. When the temperature is higher than 2070K, diamonds are completely graphitized.

[0004] The main preparation methods of existing diamond-reinforced copper-based composite materials include: pressure infiltration method / high-pressure infiltration method, SPS plasma spark sintering method, powder metallurgy method, gas pressure infiltration method, etc. The thermal conductivity of the diamond / cucr0.8 composite material prepared by the pressure infiltration method in the prior art is 620W / m·k. The equipment required for the pressure infiltration method is a vacuum hot-pressing infiltration furnace, and the pressure of the gas required for the pressure infiltration method is megapascal (MPa) level. On this basis, the prior art also uses a high-pressure infiltration method to prepare diamond / cucr0.8 composite materials, and the thermal conductivity reaches 700W / m·k. This method enables some diamonds to achieve polycrystalline. However, the diamond is partially broken during the preparation process of this method, which will affect the stability and reliability of the material. The required equipment is a special equipment, specifically a six-sided top ultra-high pressure equipment, and the required pressure is gigapascal (GPa) level, and the prepared composite material is limited to small-sized samples for experiments, which is not easy to achieve large-scale batch production. Jia Chengchang and others from Beijing University of Science and Technology also disclosed a diamond composite material with high thermal conductivity and low thermal expansion coefficient and its preparation method (Announcement No. CN101985702B), which adopts a high-temperature and high-pressure infiltration method. It is necessary to carry out ultra-high-pressure infiltration sintering at 500-2000°C and a pressure of 2-8GPa. This method is also a high-pressure infiltration method. The diamond / copper-boron and diamond / copper-zirconium composite materials prepared by the high-temperature and high-pressure infiltration method reported by He Jinshan and others from Beijing University of Science and Technology also belong to a high-pressure infiltration method. Limited by the internal cavity volume of the six-sided top equipment, the output of diamond copper-based composite materials prepared by the high-pressure infiltration method is low. The spark plasma sintering (SPS) process has the advantages of fast preparation speed, low sintering temperature, and the ability to prepare ceramic materials with high density, high strength and high hardness. The disadvantage is that it has high requirements for powder dispersibility, and it is easy to produce reactions and deterioration between particles during the preparation process. Therefore, the thermal conductivity is not high, and it is difficult to prepare thin slice samples with a thickness of less than 1mm. During the discharge sintering process, the upper and lower pressure heads are electrodes. If the sample is too thin, it is equivalent to a short circuit, and the sintering process with controlled temperature, time and pressure cannot be completed. Generally, when preparing materials using this method, a protective atmosphere is filled, and the protective atmosphere will remain inside the material, leaving a large number of closed pores, which in turn leads to low density and pores at the interface, so the thermal conductivity of the composite material is low. The reaction time of the powder metallurgy method is relatively long, and impurities are easily introduced during the ball milling and mixing process of the powder metallurgy method, making it difficult to achieve high-quality preparation of diamond copper-based composite materials; compared with other methods, especially the gas pressure infiltration method, the diamond powder in the powder metallurgy method is not densely stacked, so it is difficult to prepare high-volume fraction diamond copper-based composite materials. Compared with the materials prepared by the gas pressure infiltration method, the diamond copper composite material prepared by the powder metallurgy method has lower thermal conductivity under the same diamond particle size and volume fraction.

[0005] In summary, the existing preparation methods of diamond-copper composite materials cannot achieve the delicate molding of large-sized thin-sheet samples, and it is difficult to achieve high-quality and large-scale preparation. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a diamond / copper composite material, which can effectively solve the problems in the prior art of preparing the diamond / copper composite material by metal infiltration technology, such as high processing temperature, reduced thermal conductivity due to direct contact between diamond particles and molten copper, and uneven dispersion of diamond particles in the composite material, as well as the defect of diamond particles falling off due to non-wetting between diamond and metal matrix in the application in the field of friction.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for preparing a diamond / copper composite material, comprising the steps of ingredient mixing and hot pressing sintering;

[0009] 1. Ingredients mixing steps:

[0010] (1) Ingredients:

[0011] A matrix material is prepared, wherein the matrix material comprises: 4 Vol% to 8 Vol% of metal Ti / non-metal carbide, 0.2 Vol% to 0.4 Vol% of Cr or Mn powder, and the remainder is copper powder; the matrix material is uniformly mixed and prepared;

[0012] Take 75 Vol% of large-grain diamond and 25 Vol% of small-grain diamond and mix them evenly to prepare the reinforcement filling material;

[0013] (2) Mixing ingredients: 35 Vol% to 50 Vol% of the matrix material and 50 Vol% to 65 Vol% of the reinforcement filler material are placed in a container and mixed. After mixing, the mixture is ground in a vacuum environment filled with high-purity argon gas to obtain a mixture powder;

[0014] 2. Hot pressing sintering steps:

[0015] The mixed powder is subjected to vacuum hot pressing sintering, and the hot pressing sintering process includes the following steps:

[0016] a. Sinter from room temperature to 650℃~700℃, pressurize to 25MPa~35MPa simultaneously, and keep warm for 5~10 minutes;

[0017] b. Raise the temperature to 750℃-800℃, pressurize to 50MPa~70MPa simultaneously, and keep warm for 10~20 minutes;

[0018] c. Under vacuum, when the pressure drops to 25MPa-35MPa, turn off the heating system. When it cools naturally to below 100°C, fill the sintering furnace cavity with high-purity nitrogen. After the pressure inside and outside the cavity is equal, open the cavity to obtain the diamond / copper composite material.

[0019] Preferably, the large diamond particles in the reinforcement filling material are type Ib diamonds with a particle size of 100 μm to 300 μm; the small diamond particles are IMS-15 diamonds with an average particle size of 30 μm to 50 μm.

[0020] Preferably, the non-metallic carbide is silicon carbide powder; Ti3SiC2 is generated based on a mechanically induced self-propagating high temperature synthesis reaction, and the interface bonding strength between titanium silicon carbide and the cemented carbide matrix and diamond is good, and the thermal expansion coefficient is between the hard metal matrix and the diamond film, and can be used as an intermediate layer to relieve the internal stress at the interface between the cemented carbide matrix and the diamond film. The titanium silicon carbide generated by the reaction of titanium and silicon carbide of the present invention has higher fracture toughness and thermal stability than diamond. Therefore, combining diamond and titanium silicon carbide can improve the hardness, strength, toughness and thermal stability of the composite material.

[0021] In addition, the titanium and silicon carbide of the present invention can not only generate titanium silicon carbide, but also react with carbon atoms on the surface of diamond at high temperature to generate stable metal carbides, which can have good bonding with diamond and can be well wetted by the matrix metal, thereby enhancing the bonding force between diamond and matrix metal and reducing interface thermal resistance. A chemical bond is formed between the carbon atoms in silicon carbide and chromium or manganese, and carbon and manganese are covalently bonded, having excellent mechanical properties and thermal properties. At the same time, the microhardness of the reaction layer formed by the diffusion of copper and chromium or manganese shows that the hardness of the intermetallic compound is much higher than that of the pure copper or pure chromium or manganese metal matrix, so the intermetallic compound establishes a chemical connection between the copper metal matrix and the chromium carbide or manganese silicon.

[0022] Preferably, the particle size of the silicon carbide powder is 1.5 μm to 3.0 μm. The particle size of the copper powder is 15 μm to 30 μm. The particle size of the titanium powder is 10 μm to 30 μm. The particle size of the Cr powder or the Mn powder is 8 μm to 15 μm.

[0023] Preferably, (1) in the batching step, the volume ratio of metal Ti to non-metallic carbide is 1:4-6. (2) in the batching and mixing step, 50 Vol% of the matrix material and 50 Vol% of the reinforcement filler material are placed in a container and mixed. According to three-dimensional Euclidean space, if the diamond particles are spherical and uniform in size, the maximum volume fraction of diamond particles in the copper-based composite material is ideally about 65 vol%; but due to some experimental limitations, when diamond particles of approximately a single size are used, the copper-based composite material usually contains about 50 vol% diamond. At the same time, the two sizes of diamonds used in the present invention can obtain a high relative packing density of the copper-based composite material containing diamond, greatly reducing the porosity.

[0024] Preferably, the ingredients are mixed by rocking and vibrating for 3 to 6 hours.

[0025] Preferably, the grinding is carried out in a vacuum ball mill evacuated to 10 -2 After the solid reaches 0.04 K, high-purity argon gas is filled for ball milling. The argon gas pressure is controlled at 0.2 MPa to 0.5 MPa. The ball milling action mode is planetary ball milling, and the ball milling time is 1 to 3 hours. The ball milling process is carried out in segmented intervals to effectively adjust the surface energy state of particles of different components. For solids with T>0K, the surface Gibbs free energy can be reduced by the entropy factor [G = (U + PV) - TS = H - TS] based on the degree of surface disorder, which is achieved through the ball milling process. There is also a surface elastic strain term that is different from the surface energy, the surface stress, which can also be adjusted by ball milling. The surface energy exists because the molecules in the condensed phase attract each other. The generation of the surface involves the removal of molecular contacts (bond breaking) from above the surface, which involves energy input. Therefore, the movement in the condensed phase driven by ball milling (repetition of welding and breaking) can occur within a certain range, and this movement will continue to minimize the total surface energy γA.

[0026] Preferably, the heating rate for sintering from room temperature to 650°C to 700°C is 0.8K / s to -1.5K / s; the heating rate for heating to 750°C to 800°C is 0.05K / s to 0.1K / s.

[0027] The method for preparing the diamond / copper composite material provided in the above technical solution has the following beneficial effects:

[0028] The maximum tensile strength (UTS) of the diamond / copper composite material prepared by the method of the present invention can reach 500MPa; the coefficient of thermal expansion (CTE) is less than 9×10 -6 / K; the diamond volume ratio can be continuously adjusted in the range of 50%-65% to obtain diamond / copper composite materials with different components that match the thermal expansion coefficient (CTE) of the contact surface of the power device; the lower hot pressing sintering temperature (about 780°C) can avoid damage to the thermal properties of large-grain diamonds.

[0029] The synergistic optimization of the material components, ball milling mixing, coating and sintering processes of the present invention obtains a copper-based diamond composite material with smaller interface thermal resistance. Under the component condition of a diamond volume ratio of 50%, the room temperature thermal conductivity of the composite material reaches 715W / mK. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of the microstructure of the synthesis principle of the present invention;

[0031] Figure 2 The titanium carbide crystal structure diagram and phase diagram of the diamond / copper composite material;

[0032] Figure 3 is the silicon carbide phase diagram of diamond / copper composite;

[0033] Figure 4 is the XRD spectrum of diamond / copper composite material;

[0034] Figure 5 This is the EDS layered image of diamond / copper composite material;

[0035] Figure 6 This is an electron image of a diamond / copper composite.

[0036] Figure 7 This is a diamond distribution image of a diamond / copper composite material;

[0037] Figure 8 This is the copper distribution image of diamond / copper composite material;

[0038] Fig. 9 This is the component distribution spectrum of diamond / copper composite material. DETAILED DESCRIPTION

[0039] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.

[0040] This embodiment provides a method for preparing a diamond / copper composite material, including the steps of ingredient mixing and hot pressing sintering;

[0041] 1. Ingredients mixing steps:

[0042] (1) Ingredients:

[0043] A matrix material is prepared, wherein the matrix material comprises: 1.3 Vol% metal Ti, 5.7 Vol% silicon carbide powder (the particle size of the silicon carbide powder is 1.5 μm to 3.0 μm, and the particle size of the titanium powder is 10 μm to 30 μm), 0.2 Vol% to 0.4 Vol% Mn powder (the particle size of the Mn powder is 8 μm to 15 μm), and the remainder is pure copper powder (the particle size of the copper powder is 15 μm to 30 μm); the matrix material is uniformly mixed and prepared;

[0044] 75 Vol% of large-grain diamond (type Ib diamond, with a particle size of 100 μm to 300 μm) and 25 Vol% of small-grain diamond (IMS-15 diamond, with an average particle size of 30 μm to 50 μm) are uniformly mixed to prepare a reinforcing filler material;

[0045] (2) Mixing ingredients: 50 Vol% of the matrix material and 50 Vol% of the reinforcing filler material are placed in a container and mixed, specifically by rocking and vibrating for 3 to 6 hours; after mixing, vacuum is drawn to 10 in a vacuum ball mill. -2 After Pa, high-purity argon gas is filled in for ball milling, the argon gas pressure is controlled at 0.2MPa~0.5MPa, the ball milling action mode is planetary ball milling, and the ball milling time is 1~3 hours; after ball milling, the mixture powder is obtained.

[0046] 2. Hot pressing sintering steps:

[0047] The mixed powder is subjected to vacuum hot pressing sintering, and the hot pressing sintering process includes the following steps:

[0048] a. Sintering from room temperature to 650℃~700℃, pressurizing to 25MPa~35MPa simultaneously, and keeping warm for 5~10 minutes; and the heating rate from room temperature to 650℃~700℃ is 0.8K / s~-1.5K / s;

[0049] b. Raise the temperature to 750℃-800℃, pressurize to 50MPa-70MPa simultaneously, and keep warm for 10-20 minutes; the heating rate to 750℃-800℃ is 0.05K / s-0.1K / s;

[0050] c. Under vacuum, when the pressure drops to 25MPa-35MPa, turn off the heating system. When it cools naturally to below 100°C, fill the sintering furnace cavity with high-purity nitrogen. After the pressure inside and outside the cavity is equal, open the cavity to obtain the diamond / copper composite material.

[0051] The thermal expansion coefficient of the obtained composite material was measured using a German NETZSCH DIL 402Expedis Classic thermal expansion instrument. The thermal expansion coefficient of the sample was less than 8*10 -6 / K. Thermal conductivity is greater than 715W / m·K, and tensile strength (UTS) is greater than 500MPa.

[0052] like Figure 2 As shown, the preparation method of the present invention can obtain a titanium carbide bonding component; Figure 3 This indicates that the preparation method of the present invention can obtain titanium silicon carbide bonding components. The XRD spectrum of the obtained sample is as follows: Figure 4 As shown in the figure, it can be seen that copper has a face-centered cubic structure with a lattice constant of about 0.362nm, the lattice constant of β-cubic silicon carbide is 0.4359nm, and titanium carbide has a face-centered cubic structure with a lattice constant of 0.4329nm, and the space group is Fm3m. This structure gives titanium carbide high hardness, high melting point and good chemical stability, making it perform well in a variety of applications, such as the preparation of cemented carbide, heat-resistant alloys and high-temperature radiation materials. Figure 5It can be seen that the distribution of diamond and copper is basically uniform in the 1mm*1mm area. The appearance of oxygen content in the figure is due to the huge specific surface area of ​​the powder, which leads to enhanced oxidation in the powder mixing process.

[0053] The implementation modes of the present invention are described in detail above in conjunction with the embodiments, but the present invention is not limited to the above-mentioned implementation modes. For ordinary technicians in this technical field, after knowing the contents recorded in the present invention, they can make several equivalent changes and substitutions thereto without departing from the principle of the present invention, and these equivalent changes and substitutions should also be regarded as belonging to the protection scope of the present invention.

Claims

1. A method for preparing a diamond / copper composite material, comprising the steps of mixing ingredients and hot pressing and sintering, characterized in that:

1. Ingredients mixing steps: (1) Ingredients: A matrix material is prepared, wherein the matrix material comprises: 4 Vol% to 8 Vol% of metal Ti / non-metal carbide, 0.2 Vol% to 0.4 Vol% of Cr or Mn powder, and the remainder is copper powder; the matrix material is uniformly mixed and prepared; Take 75 Vol% of large-grain diamond and 25 Vol% of small-grain diamond and mix them evenly to prepare the reinforcement filling material; (2) Mixing ingredients: 35 Vol% to 50 Vol% of the matrix material and 50 Vol% to 65 Vol% of the reinforcement filler material are placed in a container and mixed. After mixing, the mixture is ground in a vacuum environment filled with high-purity argon gas to obtain a mixture powder; 2. Hot pressing sintering steps: The mixed powder is subjected to vacuum hot pressing sintering, and the hot pressing sintering process includes the following steps: a. Sinter from room temperature to 650℃~700℃, pressurize to 25MPa~35MPa simultaneously, and keep warm for 5~10 minutes; b. Raise the temperature to 750℃-800℃, pressurize to 50MPa~70MPa simultaneously, and keep warm for 10~20 minutes; c. Under vacuum, when the pressure drops to 25MPa-35MPa, turn off the heating system. When it cools naturally to below 100°C, fill the sintering furnace cavity with high-purity nitrogen. After the pressure inside and outside the cavity is equal, open the cavity to obtain the diamond / copper composite material.

2. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The large-grained diamond in the reinforcement filling material is type Ib diamond with a grain size of 100 μm to 300 μm; the small-grained diamond is IMS-15 diamond with an average grain size of 30 μm to 50 μm.

3. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The non-metallic carbide is silicon carbide powder.

4. The method for preparing the diamond / copper composite material according to claim 3, characterized in that: The particle size of the silicon carbide powder is 1.5 μm to 3.0 μm.

5. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The particle size of the copper powder is 15 μm to 30 μm; the particle size of the titanium powder is 10 μm to 30 μm.

6. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The particle size of the Cr powder or the Mn powder is 8 μm to 15 μm.

7. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: (1) In the batching step, the volume ratio of metal Ti and non-metal carbide is 1:4-6; (2) In the batching and mixing step, 50 Vol% of the matrix material and 50 Vol% of the reinforcement filler material are placed in a container and mixed.

8. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The ingredients are mixed by rocking and vibrating for 3 to 6 hours.

9. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The grinding is carried out in a vacuum ball mill evacuated to 10 -2 After Pa, high-purity argon gas is filled in for ball milling, the argon gas pressure is controlled at 0.2MPa~0.5MPa, the ball milling action mode is planetary ball milling, and the ball milling time is 1~3 hours.

10. The method for preparing the diamond / copper composite material according to claim 1, characterized in that: The heating rate from room temperature to 650°C to 700°C is 0.8K / s to -1.5K / s; the heating rate to 750°C to 800°C is 0.05K / s to 0.1K / s.

Citation Information

Patent Citations

  • Super-high thermal conductivity and low thermal expansivity diamond composite material and preparation method thereof

    CN101985702B

Cited By

  • Diamond / copper composite material and preparation method thereof

    CN121538489A